Case Report Sitcom Syncope – A Case Report: Sitcom Syncope – A Case Report (Bombay Hospital Journal, 2024)
Syncope is one of the common presenting symptoms in neurology clinics and emergencydepartments. Apart from the usual neurological and cardiovascular causes of syncope, thereare a few rare triggers that cause transient loss of consciousness like coughing, swallowing,micturition, defecation, and laughing. These neurally mediated syncopes are labelled as“Situational” syncope. We report a case of a 28-year-old male who presented with episodes ofdizziness, lightheadedness, and transient loss of consciousness mostly after excessivelaughter. He has had similar episodes of transient loss of consciousness and lightheadednessafter prolonged excessive laughing spells. This case is one of the very few described inmedical literature, most of which have similar presentations and findings on subsequentinvestigations.